Effect of NaHS on carbonic anhydrase activity of human erythrocyte - Bhakta, Abhijit; Bandyopadhyay, Maitreyi; Dasgupta, Sayantan; Sen, Santanu; Kumar, Arun; Biswas, Utpal Kumar (Asian Journal of Medical Sciences, 2016)
Background: In contrast to its role as poison, hydrogen sulfide (H2S) is recently considered as a gaso-transmitter which mediates important physiologic functions in humans. Evidence is accumulating to demonstrate that inhibitors of H2S production or therapeutic H2S donor compounds exert significant effects in various experimental models. Carbonic anhydrases (CA) are a group of zinc-containing metalloenzymes that catalyse the reversible hydration of carbon dioxide. CAs activity in erythrocytes (CAI and CAII) has recently been observed to be associated with various pathological conditions especially in diabetes mellitus, hypertension and lipid disorders. Alteration of this enzyme activity has been reported by the effect of advanced glycation end products methylglyoxal and reduced glutathione. Aims and Objectives: As H2S, being a mediator of many physiological functions and synthesized in vivo, may affect functions of many intracellular proteins like carbonic anhydrase, the objective of this study is to find out if there is any change in the carbonic anhydrase activity under the effect of H2S- donor NaHS in dose dependant manner using RBC model in vitro. Materials and Methods: Blood sample was collected from forty (40) numbers of healthy volunteers of 18-40 years of in heparin containing vials and packed cells were prepared immediately by centrifugation The packed erythrocytes were washed three times with normal saline and diluted (1:10) with the normal saline. One ml each of diluted packed cells was taken in eight test tubes. Serial dilutions of NaHS (1to 250 µMol/L) was added to all the test tubes except for the first test tube where only normal saline was added and incubated at room temperature for one hour. Haemolysates was prepared from the erythrocytes with equal volume of distilled water in each tube and the CA activity was determined in the haemolysates using standardized method. Results: There is significant increase of CA activity in dose dependent manner under the effect of NaHS and also compared to the activity of hemolysate prepared without NaHS. Conclusions:Our study for the first time demonstrated that the Carbonic Anhydrase activity of erythrocytes is significantly increases by the effect of NaHS and this study reveals some important biological role of H2S and carbonic anhydrase. Asian Journal of Medical Sciences Vol. 7(3) 2016 23-27